Raising “Good Vigorous Animals”: Medical Interest in Children's Health in Ontario, 1890-1930 - Lenskyj, Helen (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 1988)
ABSTRACTVitalist theories of physiology, together with notions of 'femininity' and 'masculinity,' helped to shape medical views and practices relating to children's health in Ontario at the turn of the century. In their pronouncements on sex-appropriate school programmes and curricula, doctors and medically-trained physical educators were influenced as much by socially constructed notions of the ideal feminine personality as by medical considerations such as female chest development, menstrual function and reproductive capacity. The practice of sport and physical education in most Ontario schools reflected this medical conservatism.